The Internationalization Dynamics of Character Based Education Pandemic - Dian Cita Sari; Ari Setiawan; Yuki Shiozaki; Khairunnas Rajab; Abu Yasid; Fariza MD Sham; Abdul Halim bin Ali; Makmur Harun; Sulaiman Dorloh; Azim A. Yuldashev; Muntaha; Mohd Kasturi Nor Bin Abd Aziz; Syahril Siddik; Siti Seituni; Nurul Azizah; A. Muammar Alawi; Dewi Maharani; Hajar Nurma Wachidah; Noorilham bin Ismail; A Hamid; Ummi Rasyidah; Mai Zunianti; Khairul Anwar; Afib Rulyansah; Rachman Sidharta Arisandi; Ezi Apino; Dedek Andrian; Ilham Tri Maulana; Felestin Felestin; Pipit Sari Puspitorini (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2021)
The study aims to identify the manifestation of Character Based Education Pandemic in internationalization Dynamics. It also explore concept of character as a part of pandemic process throughout human life and investigate on how pandemic plays role in character. In order to meet the purpose of the research, the qualitative approached, as it is in line with this particular study which is descriptive in nature. In accordance with many of the previous theories regarding the character based education in pandemic, it is found that the application of Character Based Education Pandemic of internationalization dynamics to be a better character. Improvement and successful program indirectly derived from manifestation of the characteristics of Character Based Education Pandemic namely faith in oneself, the aspiration towards excellence, the tenacity to challenge themselves, the engagement of support from others, and the continuous deliberate practice. Through the act of character based education, internationalization dynamics will evolve toward the betterment and so will the organization.